Road to Success for Women Lawn Tennis in India to International - Sundar Raj, N.; Sherif G F, Jamal; Ranjith, P.; S, Eswaran.; Venkatesh, A. (Journal of Neonatal Surgery, 2025)
Tennis, a racquet sport, has always been one of the few individual sports that Indians have been good at and produced good talent in; also, they have equal contributions with their male players. Tennis player’s careers were not easy in India because of no sponsorship and no encouragement from the local government; it is very difficult to move to the next level of training and traveling to tournaments. Parents were the only source of financial support. Players who want to improve their game develop speed, agility, strength, and coordination through exercise and workouts. However, the great players approach the game, especially by mental attitude. In general, when one plays regularly with different players who are more experienced as participate in higher-level competition, it is easy to improve the skills and to develop the strategies in tennis. A vital component to becoming a professional tennis player is to attack and adapt the same strategies to our strengths. Physical fitness in tennis is very important both to prevent injuries as well as to increase performance. Each player varies in their intensity and duration. The Women's Tennis Association is the main organization that works for the female tennis players, which was founded by Billie Jean King in 1973 on the principle of equal opportunity. Now the WTA is the global leader in women’s tennis professional sports. Players use the service of WTA and gain concrete skills to maximize their performance. Former tennis stars should have access to a variety of initiatives both during and after their careers, such as leadership, career mentoring, networking and legends events, coaching credentials, financial preparation and purchasing, and subsidized university education. It has been demonstrated that these methods for developing female tennis players help them stay at the top of their discipline.